Perbedaan Fungsi Kognitif Mahasiswa Fakultas Kedokteran Unissula dengan IPK Kurang dari 3 dan IPK Lebih sama dengan 3 Yudisium Tahun 2018 - Ahmadi NH; Elly Noerhidajati; Siti Maesaroh (International Consortium of Education and Culture Research Studies, 2019)
Cognitive function varies in each human being, from simple to complex, requiring attention, concentration, and coordination. Cognitive is related to a person's ability to think, solve problems, organize and also to communicate and interact with others and the environment. Methods: cross-sectional research, samples involve the students of medical faculty of Unissula-Semarang with GPA less than 3 and more than 3 graduated in 2018, instrument Mini-Mental State Examination (MMSE). Descriptive analysis and Chi-square test. Results and Discussion: samples are 56 students, the highest gender is men (51%), the range of age 18-21 years old (53.6%), the number of GPA is the same as the one below and above 3 there are 28 (50%). Test Chi Square gender difference with P value of 0.422 GPA gender does not have significant difference to the GPA, based on the age of the results of T-test p-value 0.000, showed age had significant difference to the GPA, where the age is getting younger GPA is getting better, based on the scores of MMSE test, it was obtained p 1.000, MMSE score has no significant difference with the GPA. Conclusion: Gender and MMSE value have no difference with GPA, there is difference between age and GPA, the younger the students the better GPA the students achieve.